Successful Management of Cervico-Vaginal Prolapse in Gaddi Ewe - Tyson,; sharma , Amit; Ahuja, Ankit; Sharma, Akshay; Kumar, Pravesh; Sharma, Pururava (The Indian Journal of Animal Reproduction, 2025)
A five-year-old pregnant Gaddi ewe weighing 42 kg, in her second pregnancy, was presented with signs of restless ness, straining, and a complete Cervico-vaginal prolapse that had persisted for two days. Upon physical examination, a  smooth, crimson, spherical mass was observed protruding from the vaginal canal, with no history of prolapse during her  previous lambing. Abdominal ultrasonography confirmed the presence of two viable fetuses, necessitating immediate  intervention. The treatment plan included administering caudal epidural analgesia with 2% lignocaine at a dosage of 4  mg/kg body weight, followed by cleaning and decontaminating the prolapsed mass with a mild potassium permanganate  solution. The prolapsed mass was then carefully repositioned to alleviate bladder pressure and prevent further trauma.  Finally, Buhner’s suture was applied to maintain the prolapse in place until term, with the sutures being loosened just  before lambing.
Keywords: Buhner suture; Cervico-Vaginal prolapse; Sheep